The great omission Rediscovering Jesus' essential teachings on discipleship - Willard, Dallas (San Francisco Harper Collins, 2006)
The bestselling author of "The Divine Conspiracy" reveals that being a Christian is more than a ticket to heaven--it is a lifelong process of being trained by God to be like Jesus.
Keywords: Jesus Christ -- Teachings. Christian life. Spiritual formation